Diastolic dysfunction in late postmenopausal patients with undifferentiated connective tissue disease and hypertension - A. M. Shambatov; N. V. Izmozherova; A. A. Popov; I. F. Grishina (Российский кардиологический журнал, 2023)
Aim. To assess myocardial diastolic function (DF) in late postmenopausal women with undifferentiated connective tissue disease (UCTD) and hypertension (HTN).Material and methods. This cross-sectional study included 135 postmenopausal women, the median age of which was 68 years (65÷70,5 years). The anamnesis was collected using a standardized questionnaire. Verification of UCTD was carried out according to clinical guidelines. All patients underwent standard transthoracic echocardiography. The assessment of left ventricular (LV) DF was carried out according to the transmitral flow. LV diastolic dysfunction (DD) was classified into three types: rigid, pseudonormal, and restrictive. Statistical processing was carried out in the STATISTICA 13.0 environment. The measure of data averaging is the median, the measure of dispersion is 25%÷75%. The significance of differences was assessed using the Mann-Whitney test. Differences were considered significant at p˂0,05.Results. Group 1 — 20 (14,8%) patients with verified UCTD and HTN, group 2 — 88 (65,2%) patients with HTN without UCTD, control group — 23 (30%) patients without HTN and UCTD. There were no differences in age, duration of postmenopause and body mass index between the groups. In the first group, a significant decrease in the ratio of peak early to late diastolic LV filling velocity was revealed (p˂0,01). A significant increase in left ventricular end-systolic wall stress revealed in group 1. In 108 (100%) patients, LVDD was detected; among the patients of the control group, DD was not detected. In 8 (40%) patients in group 1, a pseudo-normal type of DD was detected, while in 12 out of 20 patients (60%) — rigid type of DD. When assessing DF in patients of group 2, a significant decrease was found in the ratio of peak early to late diastolic LV filling velocity, a significant increase in LV end-diastolic wall stress and end-diastolic pressure. In 2 out of 3 (57,80%) patients of group 2, DD of the rigid type was detected, while pseudonormal type — in 32,2% of patients in this group. Group 2 patients had a significant decrease in the early diastolic mitral annular velocity (p˂0,01).Conclusion. The analysis of myocardial echocardiographic characteristics indicates a significant contribution of HTN-associated UCTD to the development of LVDD in postmenopausal women.